Landscape analysis of early childhood development and agriculture in Bangladesh, Kenya, Peru, Rwanda, and Sri Lanka - McCann, Juliet; Sproule, Katie; Bliznashka, Lilia; Olney, Deanna K. (International Food Policy Research Institute, 2023)
In low- and middle-income countries (LMIC), 40% of pre-school-aged children have poor development, which undermines educational attainment and earnings later in life. To reach their full developmental potential, children require adequate nutrition, good health, responsive care, and opportunities for early learning. Early childhood development (ECD) interventions can mitigate multiple risk factors related to responsive care and opportunities for early learning, whereas agricultural interventions can mitigate health and nutrition risk factors. In addition, organic farming and agroecological interventions more broadly can promote ECD by reducing pesticide exposure, a known environmental risk factor for poor ECD. Despite this potential of individual interventions to promote and protect ECD, evidence is lacking on the potential additive or synergistic effects of combining agricultural and ECD interventions. Moreover, little is known about the acceptability and feasibility of combining agricultural and ECD interventions among different stakeholders (e.g., beneficiaries, implementers). To date, most agricultural and ECD interventions to promote and protect child outcomes in LMICs have largely been conducted in rural settings. Thus, little is known about what the design of these types of interventions could look like in urban and peri-urban settings.